Performance of lactating dairy cows fed alfalfa haylage treated with bacterial inoculants at the time of ensilation - Scheffel, Michael V.; Scoby, R.K.; Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Sixty Holstein cows averaging 65 days in milk at the initiation of a 13-week study were used to evaluate three alfalfa haylages. Haylages were treated at the time of ensilation with either a Pioneer experimental inoculant (Treatment A), no inoculant (Treatment B), or Pioneer brand 1174® inoculant (Treatment C). Cows fed A had greater peak yields and tended to produce more milk than cows fed B and C. Milk fat percentages were 3.7, 3.66, and 3.59 for A, B, and C, respectively. Greater milk yield and butterfat percentage translated into higher (P<.05) daily fat production by cows fed A compared to C but not B.
Keywords: Lactating cows; Alfalfa haylage; Inoculant